2002
DOI: 10.1016/s0092-8674(02)00759-6
|View full text |Cite
|
Sign up to set email alerts
|

Dot1p Modulates Silencing in Yeast by Methylation of the Nucleosome Core

Abstract: DOT1 was originally identified as a gene affecting telomeric silencing in S. cerevisiae. We now find that Dot1p methylates histone H3 on lysine 79, which maps to the top and bottom of the nucleosome core. Methylation occurs only when histone H3 is assembled in chromatin. In vivo, Dot1p is solely responsible for this methylation and methylates approximately 90% of histone H3. In dot1delta cells, silencing is compromised and silencing proteins become redistributed at the expense of normally silenced loci. We sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

31
824
0
10

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 777 publications
(865 citation statements)
references
References 43 publications
31
824
0
10
Order By: Relevance
“…The multi-copy OVA-HA expression vector pFvL210 was generated by cloning of a C-terminally HA-tagged version of the chicken OVA cDNA from pAc-neo-OVA1 [64] into the BamHI site of pTCG [65]. The plasmid was transformed into yeast strain UCC7164 (a derivative of S288C) [66] and transformed cells were grown in synthetic media lacking tryptophan to select for the plasmid.…”
Section: Yeastmentioning
confidence: 99%
“…The multi-copy OVA-HA expression vector pFvL210 was generated by cloning of a C-terminally HA-tagged version of the chicken OVA cDNA from pAc-neo-OVA1 [64] into the BamHI site of pTCG [65]. The plasmid was transformed into yeast strain UCC7164 (a derivative of S288C) [66] and transformed cells were grown in synthetic media lacking tryptophan to select for the plasmid.…”
Section: Yeastmentioning
confidence: 99%
“…However, deletion of this boundary element results in only limited repression of the nearest euchromatic gene (Meneghini et al 2003). Recent work has shown that multiple euchromatin-associated factors prevent heterochromatic spread in a process termed ''anti-silencing'' (Kimura et al 2002;van Leeuwen et al 2002;Suka et al 2002;Kristjuhan et al 2003;Meneghini et al 2003;SantosRosa et al 2004;Jambunathan et al 2005). An example of one such factor is the histone H2A variant H2A.Z (Meneghini et al 2003).…”
mentioning
confidence: 99%
“…Histone H3 Lys-79 is methylated by Dot1p [60,[67][68][69], a protein originally identified as a disruptor of telomeric silencing in S. cerevisiae [70]. Methylation of H3 Lys-79 in S. cerevisiae is important for the proper localization of the SIR (silent information regulator) complex [60,69] and DNA damage signaling [71,72].…”
Section: Dot1p: Non-set Domain Hkmtmentioning
confidence: 99%
“…Methylation of H3 Lys-79 in S. cerevisiae is important for the proper localization of the SIR (silent information regulator) complex [60,69] and DNA damage signaling [71,72]. In human, mistargeting of hDOT1L to Hoxa9 (a leukemia-relevant gene) plays an important role in MLL (mixed lineage leukemia)-AF10-mediated leukemogenesish [73].…”
Section: Dot1p: Non-set Domain Hkmtmentioning
confidence: 99%
See 1 more Smart Citation